TEVAR and EVAR, the unknown knowns of the cardiovascular hemodynamics; and the immediate and long-term consequences of fabric material on major adverse clinical outcome - Sultan, Sherif; Acharya, Yogesh; Soliman, Osama; Parodi, Juan Carlos; Hynes, Niamh (Frontiers in Surgery, 2022)
This review discusses the impact of endovascular aneurysm repair on cardiovascular (CV) hemodynamics and the role of stent-graft material, i.e., polytetrafluoroethylene (PTFE) vs polyester in post-procedural outcomes. Endovascular aneurysm repair has been widely employed in the last decades for thoracic and abdominal aneurysm repair. However, aortic endografts are stiff and alter the native flow hemodynamics. This failure to simulate the native aorta could lead to added strain on the heart, manifesting as increased left ventricular strain, higher pulse pressure, and congestive heart failure later. This could result in adverse CV outcomes. Also, evidence is mounting to support the implication of stent-graft materials, i.e. PTFE vs polyester, in adverse post-procedural outcomes. However, there is an absence of level one evidence. Therefore, the only way forward is to plan and perform a randomised controlled trial to demonstrate the alterations in the CV hemodynamics in the short and long run and compare the available stent-graft materials regarding procedural and clinical outcomes. We believe the best solution, for now, would be to reduce the stented length of the aorta. At the same time, in the longer term, encourage continuous improvement in stent-graft materials and design.